PENGEMBANGAN DESA BERKELANJUTAN MELALUI ENERGI TERBARUKAN: SOSIALISASI POTENSI ENERGI ANGIN, AIR DAN PANAS BUMI - Podungge, Abdul Wahab; Ma'arif, Samsul; Nuna, Muten; Polinggapo, Jefri; Hunawa, Robby; Sahi, Nirmala; Yusufa, Nurrachmat Farhan; Prabowo, Fikodias Gilang; Safitri, Zahara; Hanggoro, Satrio; Ramadhan Al Said, Muhammad Vieryco; Nataniel, Reynald Kevin; Ayuningtias, Anggun Cahya; Anastasya, Tiara; Cahyono, Totok Hadi; Manullang, Esti Vivi; Saima, Wiranda; Olii, Erick Putra; Ramdhani, Ahmad; Ramdhani, Mohammad (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2025)
Renewable energy is an energy source obtained from natural resources that can be naturally renewed in a relatively short time, so that its availability will not run out as long as its use is carried out sustainably. This article aims to increase the understanding of the Pinomontiga Village community regarding the importance of renewable energy in improving the quality of life and supporting the local economy. The results of the activity show that: 1) The activity of cleaning up garbage on the beach in Pinomontiga Village has succeeded in increasing public awareness of the importance of maintaining the cleanliness and sustainability of the coastal ecosystem. Collaboration between residents, students, and related parties not only cleans the beach, but also fosters a sense of collective responsibility in protecting the environment. Education about the negative impacts of garbage on marine biota and the local economy, especially the fisheries and tourism sectors, is an important aspect of this activity; 2) Socialization regarding renewable energy, such as solar, wind, and biomass energy, provides new insights for coastal communities about environmentally friendly energy solutions that can be optimized for local needs. The potential for renewable energy in coastal areas opens up new economic opportunities and reduces dependence on fossil fuels; 3) Tree planting in coastal areas not only functions as a greening effort, but also helps control erosion, protect against coastal flooding, and create a healthier ecosystem. Selecting the right tree species can support the development of local wind energy, providing ecological benefits while opening up opportunities in the renewable energy sector. The results of this study indicate that a community-based approach to the application of renewable energy has great potential to increase public awareness and participation in environmental conservation. Further studies can examine the effectiveness of various strategies for implementing renewable energy in coastal communities, including technical, economic, and social aspects. In addition, a more in-depth analysis is needed regarding policies that support the sustainable use of renewable energy at the local level.